Mexico : Experiences with Pro-Poor Expenditure Policies - Corbacho, Ana (IMF Working Papers; Working Paper ;, 2002)
Against the background of Mexico's persistently high degree of inequality, this paper analyzes the country's experience with pro-poor policies over the last decade. A number of important government initiatives, implemented since the mid-1990s, have aimed at improving distributional equity through pro-poor expenditure programs, while at the same time seeking to increase the efficiency of public spending. This paper reviews these initiatives and outlines some additional policy options.